The Psychological Inflexibility in Pain Scale (PIPS) – validation, factor structure and comparison to the Chronic Pain Acceptance Questionnaire (CPAQ) and other validated measures in German chronic back pain patients - Barke, Antonia (BMC Musculoskelet Disord, 2015)
BACKGROUND: Acceptance and Commitment Therapy (ACT) for pain offers an alternative to traditional Cognitive Behavioural Therapy (CBT) approaches. ACT focuses on the enhancement of ‘psychological flexibility’ that enables individuals to pursue their values and goals despite pain. To assess specific treatment effect or mediators and moderators of change, questionnaires measuring ACT constructs are needed. METHODS: The Psychological Inflexibility in Pain Scale (PIPS) was translated into German and completed by 182 participants with chronic back pain (70.3 % women, age 51.0 ± 10.5 years). Item analyses and a confirmatory factor analysis were computed as well as correlations with the Chronic Pain Acceptance Questionnaire (CPAQ), which measures related, but slightly different ACT-related constructs, and self-reported disability, pain intensity and further pain-related questionnaires. RESULTS: The confirmatory factor analysis reproduced the original structure with two subscales and a good fit. The internal consistencies of the subscales were Cronbach’s α = .91 (Avoidance) and α = .26 (Fusion). Average item-whole correlations of the items with the respective subscales were r = .71 (Avoidance) and r = .20 (Fusion). The highest correlations were observed for Avoidance with the CPAQ (r = −.81), the Tampa Scale of Kinesiophobia (r = .58) and the Pain Catastrophizing Scale (r = .56) and for Fusion with the CPAQ subscale Pain willingness (r = −.55). The PIPS subscale Avoidance predicted pain-related disability even after controlling for catastrophizing and fear of movement. CONCLUSIONS: The PIPS subscale Avoidance may be a valuable instrument to assess treatment processes in future RCTs. The PIPS subscale Fusion seemed more problematic in the German sample with chronic back pain. More research on the comparison between PIPS and other questionnaires assessing psychological flexibility and the usefulness of the concept ‘Fusion’ for chronic pain are needed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12891-015-0641-z) contains supplementary material, which is available to authorized users.